WORKPLACE INCIVILITY: SCALE DEVELOPMENT AND VALIDATION - TURGUT, TÜLAY (My University, 2018)
The main purpose of this study is to explain the concept of workplace incivility, which is anunderestimated subject in Turkey but a popular one in the international literature and to develop a Turkishincivility scale. Workplace incivility does not intend to harm others but it harms workplace norms and putsa peaceful workplace environment into danger. For this reason, it is an important topic for the businessworld. In this study, Coworker Incivility Scale and Supervisor Incivility Scale were developed seperatelybecause workplace incivility has two different sources, coworkers and supervisor.

Bu araştırmanın temel amacı, Türkiye’de hak ettiği önemi bulmamış bir konu olan işyeri nezaketsizliğini açıklamak ve Türk kültürü için bir nezaketsizlik ölçeği geliştirmektir. İşyerlerinde karşılaşılan nezaketsiz davranışlar, karşı tarafa zarar vermeyi amaçlamasa da işyeri normlarına ve huzurlu bir çalışma ortamının yaratılmasına zarar vermektedir. Bu nedenle de iş dünyası için önem arzetmektedir. Bu çalışmada, işyerinde nezaketsizlik büyük oranda iş arkadaşlarından veya yöneticilerden geldiği için, iş arkadaşı ve yönetici nezaketsizliği olarak iki farklı ölçek geliştirilmiştir.
İŞYERİ NEZAKETSİZLİĞİ: BİR ÖLÇEK GELİŞTİRME ÇALIŞMASI
Keywords: İktisat; İşletme